A new population of parvocellular oxytocin neurons controlling magnocellular neuron activity and inflammatory pain processing - Eliava, Marina; Silva Gouveia, Miriam da; Althammer, Ferdinand; Chini, Bice; Tan, Linette Liqi; Kuner, Rohini; Grinevich, Valéry (Neuron, 2016)
Summary - Oxytocin (OT) is a neuropeptide elaborated by the hypothalamic paraventricular (PVN) and supraoptic (SON) nuclei. Magnocellular OT neurons of these nuclei innervate numerous forebrain regions and release OT into the blood from the posterior pituitary. The PVN also harbors parvocellular OT cells that project to the brainstem and spinal cord, but their function has not been directly assessed. Here, we identified a subset of approximately 30 parvocellular OT neurons, with collateral projections onto magnocellular OT neurons and neurons of deep layers of the spinal cord. Evoked OT release from these OT neurons suppresses nociception and promotes analgesia in an animal model of inflammatory pain. Our findings identify a new population of OT neurons that modulates nociception in a two tier process: (1) directly by release of OT from axons onto sensory spinal cord neurons and inhibiting their activity and (2) indirectly by stimulating OT release from SON neurons into the periphery.
Gesehen am 13.05.2019